Efektivitas Metode Role Playing Dalam Meningkatkan Hasil Belajar PPKn Pada Siswa Kelas V SDN Tolokibit - Kuatan, Adrin D; Putera, Rafh Febryan (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research aims to test the effectiveness of the Role Playing method in improving learning outcomes for Pancasila and Citizenship Education (PPKn) in class V students at SDN Tolokibit using a quasi-experimental design with a pretest-posttest group control. Two V classes were chosen randomly, where one class was treated with the Role Playing method as the experimental group, while the other class used the conventional method as the control group. The results showed that the average Posttest score of experimental group students increased by 25% from their pretest score, while the control group only experienced an increase of 10%. Observations also noted a higher level of student engagement in the experimental group, with active participation reaching 80% during the learning process, compared to 50% in the control group. Thus, the Role Playing method has proven to be effective in increasing students' understanding and involvement in Civics learning. It is recommended for teachers to consider using this method as an alternative strategy in teaching Civics in elementary schools and to train teachers in implementing the Role Playing method effectively to maximize active and interactive learning. It is hoped that the implementation of this method can make a positive contribution in efforts to improve the quality of education at the elementary level, with a focus on developing an understanding of Pancasila and citizenship values in the context of students' daily lives.